Dietary association of iron deficiency anemia and related pregnancy outcomes. Issue 8 (21st June 2021) - Zulfiqar, Hina; Shah, Imran Ullah; Sheas, Muhammad Naveed; Ahmed, Zahoor; Ejaz, Umaira; Ullah, Irfan; Saleem, Saad; Imran, Muhammad; Hameed, Muhammad; Akbar, Banaras
Abstract: Iron deficiency anemia (IDA) is a common public health occurrence of pregnancy which is particularly prevalent in developing countries like Pakistan. During this critical period, the deficiency of iron is very common as the iron requirements are greatly enhanced. IDA during pregnancy is associated with intrauterine growth retardation, premature birth, low birthweight, increased labor time, higher risk of infection, elevated maternal and prenatal mortality, muscle dysfunction, and low physical capacity. The present study was aimed to check the prevalence, effect of diet on IDA and its association with the pregnancy outcome, that is, birthweight. Five different public sector hospitals of Rawalpindi and Islamabad were analyzed. A sample size of 500 pregnant females of third trimester was observed which were then followed after delivery from September 2020 to January 2021. A well‐designed questionnaire was developed where different demographic factors, dietary recalls, biomarkers, and other determinants were obtained. The data from the questionnaires were later coded for the purpose of analysis in the statistical package (SPSS) using chi‐square test. Our study indicated that IDA is a moderate public health problem among pregnant women in twin cities and more than half of study subjects have depleted iron stores. Approximately 63% of the subjects were having iron deficiency and 24.8% were facing severe iron deficiency anemia. Only 12% of the subjects were considered as normal. The high prevalence of anemia in our subjects was probably due to low iron intake and poor dietary habits. The results of the study may not be generalizable due to time constraints and other factors. Maternal anemia still remains a major public health concern that requires more attention especially in developing and underdeveloping countries. Abstract : Maternal iron deficiency is associated with intrauterine growth retardation, premature birth, low birthweight, increased labor time, higher risk of infection, elevated maternal and prenatal mortality, muscle dysfunction, and low physical capacity. Our study indicated that IDA is a moderate public health problem among pregnant women in twin cities and more than half of study subjects have depleted iron stores. Maternal hemoglobin status was found to affect pregnancy outcome. Newborns born to women with low hemoglobin levels tended to have lower birthweight. Therefore, the etiological factors associated with maternal anemia during pregnancy in Pakistan should deserve more attention.